The history of the forming and the features of the soil, lithological and geomorphological structure of the Jizzakh steppe as the basais for its natural zoning - E. I. Pankova; D. L. Golovanov; D. A. Soloviev; I. A. Yamnova (Бюллетень Почвенного института им. В.В. Докучаева)
The paper provides initial materials characterizing the complicated history of formation, natural soils and lithological-geomorphological conditions of the Jizzakh steppe before the beginning of reclamation development. It is shown that on the basis of soil-lithological and geomorphological zoning, the Jizzakh steppe is divided into a number of natural regions belonging to different levels (altitude levels) of the piedmont plain. In total, 22 districts have been identified within the Jizzakh steppe, including the foothill margins. On the piedmont plain itself, the regions are combined into two high-altitude levels: the upper step and the lower step or blanket zone. These two levels differ sharply in terms of drainage conditions and soil salinity. The upper level, covering the upper and middle parts of the alluvial fan, the high interconal Zaamin-Sanzar plain and the Lomakino plateau, is characterized by a weak manifestation of salinity due to relatively good drainage, except for the sloping depressions of the Lomakino plateau. In contrast to the upper level, the lower level, located in the blanket zone of the piedmont plain, is characterized by active natural salinization because of the poor drainage. The saline sediments of the Zaamin cone delta are characterized by the greatest thickness. To a lesser extent, the rocks of the Sanzar cone delta, which are drained by deep gullies, are salinized. The Khavast sloping plain is characterized by a strongly saline upper two-meter layer, with salt and gypsum content decreasing with depth. Thus, it is shown that high salinity and gypsum bearing rocks, as well as high groundwater salinity of the cone delta zone are the source of modern salt accumulation in soils of foothill Golodnostepskaya plain, as well as in soils of the cone delta zone of Djizak steppe.